Impact of Cognitive Bias on the Use of Management Information Systems in Nepalese Commercial Banks - Adhikari, Shankar Nath (Journal of Business and Management, 2025)
Background: Management Information Systems (MIS) play a critical role in enhancing decision-making and operational efficiency in the banking sector. However, the effectiveness of these systems is often undermined by cognitive biases that distort how individuals process and respond to system-generated information. In the context of Nepalese commercial banks, where MIS adoption is increasing, the role of cognitive bias remains underexplored and insufficiently addressed in both research and practice. Objectives: This study aims to investigate the extent to which cognitive biases anchoring bias, overconfidence bias, loss aversion, and confirmation bias impact the use and effectiveness of MIS in Nepalese commercial banks. The goal is to identify how these psychological factors influence user interaction with MIS and their subsequent decisions. Methods: A quantitative descriptive-correlational research design was used, employing a structured 23 item questionnaire based on validated constructs. A purposive sample of 571 participants, 371 banking customers and 200 employees from Nepalese commercial banks was selected to gather diverse perspectives on MIS usage and cognitive biases. Data analysis involved SPSS 26.0 for descriptive statistics and AMOS 26.0 for confirmatory factor analysis (CFA) and structural equation modeling (SEM) to evaluate model fit and test the hypothesized relationships between cognitive biases and MIS utilization. Results: The study found that cognitive biases limit the effective use of MIS. Overconfidence, anchoring, loss aversion, and confirmation bias affect user decisions. These biases lead to ignored alerts, trust on early data, fear of change, and resistance to updates. Conclusion: Cognitive biases are critical impairments to MIS effectiveness in Nepalese commercial banks. Addressing these through targeted training, cognitive debiasing, and user-centric system design is essential to promote rational decision-making and optimize MIS utility. JEL Classification: G21, M15, D83, C38, O33